HISTORY OF ANCIENT PERIOD MUSIC CULTURE INSTRUMENTS IN CENTRAL ASIA - Xamidov Shirmamat O‘roqovich (Journal Park Publishing, 2024)
In this article the process of formation of music culture in our country from ancient times. In particular, the history of the injury of musical instruments is illuminated.
Keywords: Afrasiab (Samarkand), Asian harp, Marv, Ur Dinastia, Terracotta, ud, harp.